An R2R3-MYB Transcription Factor Positively Regulates the Glandular Secretory Trichome Initiation in Artemisia annua L. - Qin, Wei; Xie, Lihui; Li, Yongpeng; Liu, Hang; Fu, Xueqing; Chen, Tiantian; Hassani, Danial; Li, Ling; Sun, Xiaofen; Tang, Kexuan (Frontiers in Plant Science, 2021)
Artemisia annua L. is known for its specific product “artemisinin” which is an active ingredient for curing malaria. Artemisinin is secreted and accumulated in the glandular secretory trichomes (GSTs) on A. annua leaves. Earlier studies have shown that increasing GST density is effective in increasing artemisinin content. However, the mechanism of GST initiation is not fully understood. To this end, we isolated and characterized an R2R3-MYB gene, AaMYB17, which is expressed specifically in the GSTs of shoot tips. Overexpression of AaMYB17 in A. annua increased GST density and enhanced the artemisinin content, whereas RNA interference of AaMYB17 resulted in the reduction of GST density and artemisinin content. Additionally, neither overexpression lines nor RNAi lines showed an abnormal phenotype in plant growth and the morphology of GSTs. Our study demonstrates that AaMYB17 is a positive regulator of GSTs’ initiation, without influencing the trichome morphology.